Between Argumentation and Persuasion in the Pluralist and Democratic Society: About Virtues and Abilities of Critical Thinking - Lubowicka, Grażyna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2020)
The aim of the paper is to highlight transgressions which present a challenge to education and reside in the skills relating to the way of thinking both of an individual and in use in public discourse. The area of this way of thinking which is decisive of transgression and, at the same time, increases the competence of the individual who takes part in social decision making is moral judgement in situation – also a form of critical thinking – which is here discussed with reference to the philosophy of Paul Ricoeur.
Keywords: pluralism; democracy; moral judgement in situation; critical thinking; argumentation; persuasion; impartiality